If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + 2 = -2(3y + 17) Reorder the terms: 2 + -2y = -2(3y + 17) Reorder the terms: 2 + -2y = -2(17 + 3y) 2 + -2y = (17 * -2 + 3y * -2) 2 + -2y = (-34 + -6y) Solving 2 + -2y = -34 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 2 + -2y + 6y = -34 + -6y + 6y Combine like terms: -2y + 6y = 4y 2 + 4y = -34 + -6y + 6y Combine like terms: -6y + 6y = 0 2 + 4y = -34 + 0 2 + 4y = -34 Add '-2' to each side of the equation. 2 + -2 + 4y = -34 + -2 Combine like terms: 2 + -2 = 0 0 + 4y = -34 + -2 4y = -34 + -2 Combine like terms: -34 + -2 = -36 4y = -36 Divide each side by '4'. y = -9 Simplifying y = -9
| 11-x/4=2-x | | 84=(2w+2)w | | 5B-52=93 | | m^2+4m+4= | | 10-x-3=5x-13-4x | | 6(5x+6)=1-5x | | x^2=2.89 | | 13.50+74=85.7 | | -8x=-2x+4x | | 15x+0.5=25x+0.25 | | 3y^4-(4y^4+3)= | | 7b-9=5b+13 | | 45p=180 | | 3c(4c+6)-18=168 | | 5(8+9d)=-21 | | 3(6x-12)=2x+44 | | 8x-5x=33 | | 11(y-3)=7(2-3h) | | 6k-3(k-8)=162 | | 4(x-10)=-3(2-x)-x | | 6=-4.9t^2 | | -3x-3y=-3 | | 3b^2=10b | | 7y+2.9=8y+5.9 | | (2x+101)=(4x+55) | | 3x+16+5x-10=180 | | F(-4)=x^2+4 | | 12y+5x=2 | | 1-m^12= | | 47+11n=-2(1-9n) | | 1-m^2= | | -5+6+2k-3k-=k-8 |